Implementation of Digital Marketing Strategies to Increase Sales during the Covid-19 Pandemic - Aidil Amin Effendy; Mahnun Mas’adi; Heri Murtiyoko (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the implementation of digital marketing strategies and how effective digital marketing strategies are to increase sales during the Covid-19 pandemic (Studies on SMEs in South Tangerang City). This research method uses qualitative methods by gaining a deep understanding of data collection techniques through observation, documentation, and interviews, using the semi-structured interview method based on predetermined interview guides for several informants to MSME actors in the city of South Tangerang. The analysis results from the interviews show that the most effective and efficient marketing is done digitally / online, primarily through digital/online marketing. According to MSME Players in South Tangerang, they prefer to market their products through Facebook, Instagram, and Online Shop, then WhatsApp, and there are also MSME players marketing them through GoFood and GrabFood. Furthermore, the results of interviews with other informants regarding the determinants of MSMEs increase their sales during the Covid-19 Pandemic, namely promotion factors, with digital/online marketing and competitive price factors.